2020
DOI: 10.1128/msphere.00433-20
|View full text |Cite
|
Sign up to set email alerts
|

Host-Induced Genome Instability Rapidly Generates Phenotypic Variation across Candida albicans Strains and Ploidy States

Abstract: Candida albicans is an opportunistic fungal pathogen of humans that is typically diploid yet has a highly labile genome tolerant of large-scale perturbations including chromosomal aneuploidy and loss-of-heterozygosity events. The ability to rapidly generate genetic variation is crucial for C. albicans to adapt to changing or stressful environments, like those encountered in the host. Genetic variation occurs via stress-induced mutagenesis or can be generated through its parasexual cycle, in which tetraploids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 56 publications
(97 reference statements)
1
21
0
Order By: Relevance
“…In addition to higher mutation rates, tetraploid cells also frequently undergo random chromosome loss and reduce in genome size under a diverse set of growth conditions in vitro and in vivo (Bennett and Johnson 2003; Forche et al 2008; Hickman et al 2015; Gerstein et al 2017; Avramovska and Hickman 2019; Smith and Hickman 2020). Interestingly, we found that many of the tetraploid-evolved lines rapidly reduced in genome size by day 10, a timepoint prior to when we first observed any detectable caspofungin adaptation (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to higher mutation rates, tetraploid cells also frequently undergo random chromosome loss and reduce in genome size under a diverse set of growth conditions in vitro and in vivo (Bennett and Johnson 2003; Forche et al 2008; Hickman et al 2015; Gerstein et al 2017; Avramovska and Hickman 2019; Smith and Hickman 2020). Interestingly, we found that many of the tetraploid-evolved lines rapidly reduced in genome size by day 10, a timepoint prior to when we first observed any detectable caspofungin adaptation (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have shown that nematode and murine host environments induce C. albicans genome instability compared to in vitro [14][15][16][17][18] , but the specific host attributes driving genome instability have yet to be elucidated. Here, we tested whether components of host innate immune function contributed to host-associated genome instability by comparing the frequency of loss-of-heterozygosity (LOH) between C. albicans extracted from healthy and immunocompromised hosts (Fig.…”
Section: Host Defense Pathways Elevate C Albicans Genome Instabilitymentioning
confidence: 99%
“…This genetic variation may be a direct consequence of the stressors C. albicans encounters in the host which include immune stressors and other microbes. Recent work has demonstrated the host environment elevates genome instability in C. albicans similar to in vitro stressors [14][15][16][17][18] . However, the specific host components that generate this instability is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations